Comparison of stabilizers between hydrated lime and rice hull ash for subgrade improvement in clayey soils - Quilla Romero, Nuria de los Angeles; Mamani Mamani, Luis Yovanny; Ibárcena Ibárcena, Valkiria (LACCEI, 2025)
Unpaved roads with clayey soil when subjected to vehicular loads are the most likely to have problems of resistance and durability, in addition, their high content of fines will cause the emission of dust, contaminating society and the environment. The project aims to analyze the results between the stabilizers of hydrated lime (HL) and rice husk ash (RHA) through geotechnical tests carried out in the laboratory. In this research, to know their physical-mechanical properties, the tests of moisture content, granulometric analysis, Atterberg limits, modified proctor, and CBR were carried out on the soil sample by adding 8% and 12% of hydrated lime and rice husk ash. The results adding RHA, did not present LL and LP, a maximum dry density (DMS) of 1.58 g / cm3 with an optimal moisture content (CHO) of 19.30% and a CBR of 18.41%, on the other hand, with HL had a LL of 32%, LP of 29% with a IP of 3%, a maximum dry density (DMS) of 1.64 g / cm3 and an optimal moisture content (CHO) of 20.70% and a CBR of 35.07%. It is concluded that there were improvements with the percentages of addition concerning the sample in its natural state without additions, but the most effective in improving the physical properties of the soil was rice husk ash (RHA) and in the mechanical properties of the soil was hydrated lime (HL) both with an addition of 12%.